Hepatitis C Seroprevalence Among Consecutive Labor and Delivery Admissions in Two New York City Hospitals. (23rd October 2020) - Kushner, Tatyana; Park, Claire; Masand, Dana; Wagner, Brian; Grace, Marie; Rosenbluth, Emma; Rodriquez-Rivas, Clara; de la Cruz, Hernis; Overbey, Jessica; Sperling, Rhoda
Abstract: Background: Rates of hepatitis C virus (HCV) among women of childbearing age have increased as a result of the opioid epidemic, especially in the nonurban white population. Recently updated US Preventative Services Task Force and Centers for Disease Control and Prevention guidance have recommended universal HCV screening during pregnancy, but obstetrics societies have not yet endorsed this recommendation. We evaluated the seroprevalence of HCV among pregnant women in an inner-city population, compared rates with other sexually transmitted infections (STIs) screened for during pregnancy, and evaluated factors associated with HCV positivity. Methods: We performed a prospective seroprevalence study of consecutive labor and delivery admissions (both antepartum complications and delivery admissions) by testing serum samples for HCV antibody over 9 months at 2 major hospital settings in New York City. Results: Fifty-six of 7373 (0.75%; 95% confidence interval [CI], 0.57–0.98) patients screened positive for HCV, with 28 of 4013 (0.70%; 95% CI, 0.46%–1.01%) and 28 of 3413 (0.82%; 95% CI, 0.55%–1.18%) at each hospital. Forty-one percent of HCV-positive patients had any reported HCV risk factors. Hepatitis C virus-positive patients were less likely to have private insurance and more likely to have a history of cannabis, cocaine, and injection drug use ( P < .001). The HCV rates were higher among antepartum admissions compared with delivery admissions and higher than that of hepatitis B virus (0.65%; 95% CI, 0.48–0.86), human immunodeficiency virus (0.27%; 95% CI, 0.16–0.42), and syphilis (0.16%; 95% CI, 0.08–0.28). Conclusions: We found a higher than expected HCV seroprevalence among pregnant women and higher than most other STIs routinely screened for in pregnancy. Most patients had no risk factors. These findings support universal screening for hepatitis C during pregnancy. Abstract : A higher than expected seroprevalence of hepatitis C was found among pregnant women, many without known risk factors, in a prospective study of consecutive labor and delivery admissions.